IMPLEMENTATION OF VILLAGE HEAD SELECTION USING ELECTRONIC VOTING (E-VOTING) METHODS IN INDRAGIRI HULU DISTRICT - Yusnedi, Yusnedi; Utami, Sabrina; Heriasman, Heriasman (LPPM Press STIE Indragiri Rengat, 2020)
This research was conducted in Indragiri Hulu district, where this research used three villages that held head selection by using electronic voting, there are: Sidomulyo, Sungai Baung and Batu Gajah. This research used qualitative descriptive approach with the consideration that the researcher intends to obtain a picture of the Community Readiness for the Implementation of Village Head Election using the Electronic Voting (E-Voting) method in Indragiri Hulu District. This research used observation, interviews and documentation to collected all the data. The results of this study indicate that the application of the use of electronic voting in the three villages is already good, where this is indicated by the majority of the community that can already use the e-voting tool. only a small portion of the community still does not understand how to use it.